2013
DOI: 10.1097/prs.0b013e3182958796
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Harvest and Processing Techniques for Fat Grafting and Adipose Stem Cell Isolation

Abstract: Ultrasound- and suction-assisted lipoaspiration yielded similar retention of fat grafts in a xenograft model. Processing with cotton gauze rolling may be best suited for grafting cosmetically sensitive areas of the body in which optimal retention is critical and lower total graft volumes are needed. Filtration and centrifugation both effectively removed fluid fractions and resulted in comparable graft retention, and are more feasible when larger volumes are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 23 publications
(24 reference statements)
0
83
2
3
Order By: Relevance
“…82,84,[92][93][94][95][96] Of these techniques, only Telfa rolling has any evidence of improved retention over centrifugation, based on studies conducted in the nude mouse xenograft model. 84,97,98 However, the lack of human clinical trials also limits the generalizability of these findings.…”
Section: Emerging Strategiesmentioning
confidence: 97%
See 1 more Smart Citation
“…82,84,[92][93][94][95][96] Of these techniques, only Telfa rolling has any evidence of improved retention over centrifugation, based on studies conducted in the nude mouse xenograft model. 84,97,98 However, the lack of human clinical trials also limits the generalizability of these findings.…”
Section: Emerging Strategiesmentioning
confidence: 97%
“…[81][82][83] Similarly, no differences have been seen in animal studies of ultrasound-assisted harvest. 84 No significant human or animal trials exist for mechanical or laser-assisted liposuction, but in vitro studies have revealed a lower stem cell yield and poorer ASC proliferation. 85,86 Preliminary in vitro and rodent studies with water-jet-assisted liposuction suggest that it improves ASC content, results in more viable adipocytes, and increases volume retention of grafts.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…Recent literature by Rubin and colleagues has suggested that the quality of fat and its in vivo result are fairly equally comparable between washing/filtration methods and centrifugation methods. 12 Additionally, there is variability of operating room charges between different hospitals. The cost of our flagship hospital where the majority of these cases were performed may have higher charges in comparison to other hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…35 The adipose tissue was collected using an inline TissuTrans Filtron canister with filter pore sizes of 500 and 800 um. Unfiltered and filtered sample of the material remaining in the filter after removal of the filtrate was collected.…”
Section: Comparison Of Cannulas With Different Aperture Sizesmentioning
confidence: 99%